"It wasn't feasible for us": Queer Women of Color Navigating Family Formation. Issue 1 (21st February 2018) - Karpman, Hannah E.; Ruppel, Emily H.; Torres, Maria
Abstract : Objective: This intersectional analysis was designed to explore how lesbian, bisexual, and queer (LBQ) women of color understand and navigate family formation decisions. Background: Family formation research centers White heterosexual parents and heteronormative pathways (i.e., adoption and cryobank purchased sperm). Choosing a known donor may be a way for LBQ women of color to circumvent a process that has not been responsive to their needs. Method: Our qualitative analysis of 13 interviews of LBQ parents in families of color examined (a) the processes through which queer women of color arrive at the selection of a known donor, (b) the characteristics that queer women of color prioritize in donor selection, and (c) how women's interactions with external institutions (e.g., cryobanks) and histories of oppressive racialized family formation practices influence their decision‐making. Results: Participants arrived at the selection of known donors because the desired donor characteristics were unavailable through commercial sperm banks, particularly with regard to the intersection of a person who could be known and mirrored specific racial, ethnic, and cultural characteristics. This decision was highly connected to their individual identities and the intersections of those identities. Conclusion: LBQ women of color may choose known sperm donors and seek to minimize their use of biotechnology because they do not consider other alternatives (e.g., bank‐acquired sperm) desirable or feasible. Implications: Findings invite the reimagination of a cryobanking system that operates on a relational rather than biomedical model and the need for services that practice outside of White, heteronormative paradigms.